Optoacoustic imaging of naphthalocyanine: Potential for contrast enhancement and therapy monitoring - Beziere, Nicolas; Ntziachristos, Vasilis (Journal of Nuclear Medicine, 2015)
We investigated in vitro and in vivo the optoacoustic responses of silicon 2,3-naphthalocyanine bi(trihexylsilyloxide) (SiNc), considered herein as a reporter molecule for optoacoustic imaging, elucidating its efficiency for optoacoustic (photoacoustic) signal generation and examining the in vivo performance achieved. Methods: SiNc solutions were prepared using Cremophor EL in water and evaluated for light-absorbing and optoacoustic contrast-generating properties. Photostability and singlet oxygen generation were investigated under pulsed laser illumination and validated using photoabsorbance. HT-29 mouse tumor models were used to assess the biodistribution of the compound and its performance as an optoacoustic contrast agent in vivo. Results: SiNc was found to generate superior optoacoustic signals compared with the commonly used indocyanine green. Multispectral optoacoustic tomography of mouse tumors efficiently resolved the biodistribution of SiNc and the underlying perfusion parameters in vivo. In addition, we demonstrate how light-triggered SiNc reactions with molecular oxygen can be potentially sensed and discuss the relation of these measurements to the biochemical process involved in photothermal treatment. Conclusion: SiNc appears to be a promising family of contrast agent for optoacoustic imaging. Further development possibilities promise to expand its use in purely contrast generation settings, as well as its photodynamic therapy application.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Imaging; Naphthalocyanine; Optoacoustic; Photoacoustic; Photodynamic therapy